Transcriptome and metabolite analyses indicated the underlying molecular responses of Asian ginseng (Panax ginseng) toward Colletotrichum panacicola infection - Xia, Jinglin; Liu, Ning; Han, Junyou; Sun, Jingyuan; Xu, Tianyi; Liu, Shouan (Frontiers in Plant Science, 2023)
Panax ginseng Meyer is one of the most valuable plants which is widely used in China, while ginseng anthracnose is one of the most destructive diseases. Colletotrichum panacicola could infect ginseng leaves, stems and causes serious anthracnose disease with still unknown mechanism. Here, transcriptomic and metabolism analysis of the host leaves were conducted to investigate ginseng defense response affected by C. panacicola. Upon C. panacicola infection, ginseng transcripts altered from 14 hours to 24 hours, and the expression of many defense-related genes switched from induction to repression. Consequently, ginseng metabolites in flavonoids pathway were changed. Particularly, C. panacicola repressed plant biosynthesis of the epicatechin and naringin, while induced plant biosynthesis of glycitin, vitexin/isovitexin and luteolin-7-O-glucoside. This work indicates C. panacicola successes infection P. ginseng by intervening the transcripts of defense related genes and manipulating the biosynthesis of secondary metabolites which might have antifungal activities.